Burden of disease associated with dietary exposure to carcinogenic aflatoxins in Portugal using human biomonitoring approach. (August 2020) - Martins, C.; Vidal, A.; De Boevre, M.; De Saeger, S.; Nunes, C.; Torres, D.; Goios, A.; Lopes, C.; Alvito, P.; Assunção, R.
Graphical abstract: Highlights: Portuguese population is exposed to aflatoxins, carcinogenic toxins to humans. Human biomonitoring studies contribute to an accurate estimation of the burden. Exposure to aflatoxins of Portuguese population results in 172.8 Disability-Adjusted Life Years. Abstract: Human biomonitoring is an important tool to assess human exposure to chemicals, contributing to describe trends of exposure over time and to identify population groups that could be under risk. Aflatoxins are genotoxic and carcinogenic food contaminants causing hepatocellular carcinoma, the third leading cause of cancer deaths worldwide. In Portugal, scarce data are available regarding exposure to aflatoxins and no previous study used human biomonitoring data to comprehensively characterize the associated burden of disease. 24 h urine and first-morning urine paired samples were collected by 94 participants and were analyzed by liquid chromatography–tandem mass spectrometry for the quantitative determination of aflatoxins (B1, B2, G1, G2 and M1 ). Deterministic and probabilistic models were developed to assess the Portuguese exposure to aflatoxins and to estimate the health impact of this exposure, estimating the attributed Disability-Adjusted Life Years (DALYs). Aflatoxins were detected in a maximum of 13% (AFB1 ), 16% (AFB2 ), 1% (AFG1 ), 2% (AFG2 ) and 19% (AFM1 ) of the urine samples. Data obtained through the probabilistic approach revealed an estimated mean probable daily intake of 13.43 ng/kg body weight per day resulting in 0.13 extra cases of hepatocellular carcinoma, corresponding to mean annual DALYs of 172.8 for the Portuguese population (10 291 027 inhabitants). The present study generated for the first time and within a human biomonitoring study, reliable and crucial data to characterize the burden associated to the exposure to aflatoxins of the Portuguese population. The obtained results constitute an imperative support to risk managers in the establishment of preventive policy measures that contribute to ensure public health protection.